Stick2Hockey - Slade, D. (Stick2Hockey, 2010)
In Stick2Hockey, players learn the strategies, skills and `feel` of hockey in a challenging and fun environment. * New Concepts in Coaching - Revolutionary new method for coaching hockey and learning strategic concepts of team sports endorsed by Hockey New Zealand, featuring an easy-to-use interface; live action footage of skills and games, and animated drill diagrams. * Clear Interface - The clean, simple layout and easy-to-use navigational system of Stick2Hockey, gives you fast access to individual sections or a seamless journey through the content. * Animated Drills - The drills and games outlined in Stick2Hockey have been animated to illustrate the required equipment and the individual roles of participating players. * Live Action Video - Activities in Stick2Hockey have supplementary video footage to enhance understanding beyond the animated sequences. This footage also features narration from the author, guiding you through each step of the drill or skill being executed.